Test bed for farm vehicle onboard hydrogen production system with microwave plasma - Fuen, Chen; Longhan, Chen; Xin, Xie; Xiang, Li; Lan, Yubin (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Energy conservation and emission reduction are the focus worldwide. Farm vehicle engine would be more efficient if it is injected a little hydrogen during work, meanwhile, the emission of the vehicle would be decreased. Nowadays, there are many kinds of onboard hydrogen production methods, among which the microwave plasma method is regarded as the best. In order to develop an onboard hydrogen production system using microwave plasma, a new corresponding test bed was designed and developed in this research. The ethanol, water and air from the three supply pipelines were mixed and evaporated into gas mixture, and then the mixture was further created into hydrogen through microwave plasma reaction. In the test bed, a hydrogen production environment required for the reaction was provided, and hydrogen would come into being when the air was broken down by the plasma under the conditions of 0.1-0.7 atm. Furthermore, the reaction conditions could be controlled precisely, and real-time environmental data and spectral data could be collected during the hydrogen production. The experimental results showed that onboard hydrogen production could be achieved on this test bed, and the hydrogen amount produced could be adjusted to simulate real vehicle working conditions. In addition, the system is of rapid response, high precision and reliability, which can be applied in new products developments of the onboard hydrogen production system.Keywords: hydrogen production, test bed, microwave, plasma, farm vehicle, emission, steam reforming, partial oxidationDOI: 10.3965/j.ijabe.20160906.2112Citation: Chen F E, Chen L H, Xie X, Li X, Y B Lan. Test bed for farm vehicle onboard hydrogen production system with microwave plasma. Int J Agric & Biol Eng, 2016; 9(6): 65-74.